Physiological and morphological traits associated with adaptation of lucerne (Medicago sativa) to severely drought‐stressed and to irrigated environments. (2nd November 2012) - Annicchiarico, P.; Pecetti, L.; Tava, A.
Abstract Adaptation to severe drought and to irrigated cropping can both contribute to increased water use efficiency of lucerne, but knowledge on the relevant adaptive traits is limited. Five cultivars featuring contrasting adaptive responses for 3‐year forage yield across 10 agricultural environments of the western Mediterranean basin were currently studied, to identify physiological and morphological traits associated with specific and wide‐adaptation responses. The landraces Mamuntanas, Demnat 203 and Erfoud 1, and the varieties SARDI 10 and Prosementi, were grown in replicated metal containers (55 cm long × 12 cm wide × 75 cm deep; 21 plants per container) under irrigation (weekly restoring soil field capacity) and under moderate and severe drought stress (implying decreased irrigation for 30 days followed by withheld irrigation for 33 and 58 days, respectively). Cultivar post‐stress survival reflected the known cultivar adaptation to drought‐prone agricultural environments. Demnat 203, specifically adapted to irrigated, frequently mown environments, displayed higher amounts of starch, soluble proteins and total nitrogen in the crown and the root under irrigation. This was due to outstanding organ size and, for starch, higher concentrations. Mamuntanas, specifically adapted to drought‐prone environments, exhibited high water‐soluble carbohydrate concentration in storage organs under severe stress, along with a water‐conservation strategy implying less water used in initial drought‐stress phases due to limited early root development that resulted in more water available under severe stress. Drought‐tolerant germplasm also displayed lower wilting under early stress, more plants with green tissues under severe stress, and more stems per plant in stress or favourable conditions. Multivariate patterns of cultivar variation for physiological and morphological traits were strictly associated with cultivar variation for adaptation pattern. Our results highlighted the difficulty to combine some traits of environment‐specific adaptive value into a unique widely adapted variety, supporting the selection of varieties specifically adapted to irrigated or severely drought‐prone environments.